2020
DOI: 10.1038/s41598-020-71311-4
|View full text |Cite
|
Sign up to set email alerts
|

3-T T2 mapping magnetic resonance imaging for biochemical assessment of normal and damaged glenoid cartilage: a prospective arthroscopy-controlled study

Abstract: This study evaluated the ability of T2 mapping to assess the glenoid cartilage using arthroscopy as the gold standard. Eighteen consecutive patients (mean age: 52.4 ± 14.72 years, including 12 men) with shoulder pain underwent T2 mapping at 3-T with subsequent shoulder arthroscopy. With correlation to cartilage-sensitive morphologic sequences regions-of-interest were placed in the corresponding T2 maps both in normal-appearing cartilage and focal cartilage lesions using a quadrant-wise approach. Inter-reader a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Felix et al and Mittal et al got the same conclusion and showed that the T2 value of fibrocartilage injury was higher than that of normal fibrocartilage. [ 12 , 13 ] The increase of T2 value is related to the decrease of collagen fibers and proteoglycans and the increase of water content. Both human and animal experiments showed that the T2 value of fibrocartilage had a direct correlation with proteoglycans and water content.…”
Section: Discussionmentioning
confidence: 99%
“…Felix et al and Mittal et al got the same conclusion and showed that the T2 value of fibrocartilage injury was higher than that of normal fibrocartilage. [ 12 , 13 ] The increase of T2 value is related to the decrease of collagen fibers and proteoglycans and the increase of water content. Both human and animal experiments showed that the T2 value of fibrocartilage had a direct correlation with proteoglycans and water content.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [ 14 ] compared the median T2 values of patients with glenohumeral osteoarthritis to patients with normal macroscopic cartilage and demonstrated significantly higher total (glenoid and humeral head combined) T2 values for patients with osteoarthritis (median 37.52 ms; range 36.84–39.11 ms) compared to patients without (median 36.00 ms; range 33.89–37.31 ms). Wuennemann et al [ 21 ] examined the ability of T2 mapping MRI to detect focal changes in glenohumeral cartilage, with validation performed by arthroscopy in 18 patients (5 with cartilage lesions). They found that T2 mapping mean values were significantly higher in the locations of the Outerbridge grades 1–3 lesions (44.7 ± 3.7 ms) than in regions of cartilage that appeared healthy on arthroscopic examination (23.0 ± 3 ms).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, due to the thick-slice images and lack of precise shoulder landmarks visible on the T2 mapping images evaluation of additional, smaller subregions of the humeral head and glenoid cartilage was not performed as part of this work. Smaller subregions have been used previously in the study of focal glenoid cartilage defects and would be beneficial for detecting more localized changes [ 21 ]. Use of high-resolution sequences along with the T2 mapping sequence could address this challenge in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on anatomical studies, we assumed that normality is a CWI 1, indicating that thickness of anterior and posterior glenoid cartilage in healthy individuals is equal. 37 …”
Section: Methodsmentioning
confidence: 99%